ANALISIS PENGARUH BUDAYA & KELUARGA TERHADAP ORIENTASI WIRAUSAHA ORANG MUDA DI INDONESIA DAN MALAYSIA - Utama, Yosua Yudaikawira (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
This study aims to identify differences in the entrepreneurship orientation of youth people in Indonesia and Malaysia by country, different family backgrounds (business and non-business), and based on business learning experience independently when they are still in school.This study adopted the instrument used in the study of Lee and Pathak (2011) on the relationship between culture and student entrepreneur orientation originating from several countries. Also, we use Hofstede's cultural dimensions to help identify comparative analysis results. Data collection was done by distributing questionnaires online to students at several universities in Indonesia and Malaysia. The number of respondents was 223 persons consisting of 109 Indonesian respondents and 114 Malaysian respondentsIn this research, we use descriptive statistic and ANOVA to help analyze the data. The calculation shows that there are differences in entrepreneurship orientation behavior between Indonesian respondents and Malaysian respondents as a whole regarding the orientation of entrepreneurship based on country. Based on the family background of entrepreneurship and business learning experience since school, only two out of four variables that show differences in behavior between respondents who come from the background of business families with the non. In addition, the study also shows that Hofstede's cultural dimension in a country does not always affect the entrepreneurial behavior of a person living in that country.Keyword: Entrepreneurial Orientation, Hofstede Cultural Dimensions, Entrepreneurship Behavior, Family, Business learning experience, ANOVA